Semantics-based services for a low carbon society: An application on emissions trading system data and scenarios management. (February 2015) - Camporeale, Cecilia; De Nicola, Antonio; Villani, Maria Luisa
Abstract: A low carbon society aims at fighting global warming by stimulating synergic efforts from governments, industry and scientific communities. Decision support systems should be adopted to provide policy makers with possible scenarios, options for prompt countermeasures in case of side effects on environment, economy and society due to low carbon society policies, and also options for information management. A necessary precondition to fulfill this agenda is to face the complexity of this multi-disciplinary domain and to reach a common understanding on it as a formal specification. Ontologies are widely accepted means to share knowledge. Together with semantic rules, they enable advanced semantic services to manage knowledge in a smarter way. Here we address the European Emissions Trading System (EU-ETS) and we present a knowledge base consisting of the EREON ontology and a catalogue of rules. Then we describe two innovative semantic services to manage ETS data and information on ETS scenarios. Highlights: A semantics-based approach for the Low Carbon Society is proposed. A Knowledge Base for the Emissions Trading System (ETS) is presented. Ontological foundations of the ETS ontology (EREON) are described. Rules Taxonomy and Rules Catalogue are the basis for the semantic services.